Dealing with Disturbances in the Food Supply Chain for Perishable Products - Li, Haihan (2020)
Abstract Purpose: The purpose of this dissertation is to explore the disturbances (i.e. risks and uncertainties) faced by wholesalers, retailers and caterers in the perishable food supply chain and investigate how organisations deal with those risks and uncertainties to mitigate the impacts. Methodology: Qualitative research methods adopted in this research, twenty in-depth semi-structured interviews conducted with 15 companies in the fresh food industry based on the UK and China to enrich the framework with new findings. Findings: Through the interviews, the research list the common risks and uncertainties in operations with pieces of evidence, also provides new insights to the disturbances that perishable food supply chain faces and the impacts with the current hot topics such as the spread of COVID-19. Besides, the current status of the perishable food industry presented to investigate the internal cause of the vulnerability. Meanwhile, the methods that companies take to deal with the disturbances and the effect discussed. Research limitations/implications: Due to the time and resource limitation, only 15 companies invited to this study, with 90% SMEs. All the participants are focused on seafood or fruit and vegetable products. Also, the findings were only found through qualitative approaches, which lack of data support, and may remain bias from participants experience and personal views. Originality/Value: This dissertation forms a new conceptual framework of disturbances in perishable food supply chain with “supply-side disturbances”, “demand-side disturbances” and “operational disturbances” and the relationship among disturbances, risks and uncertainties were clarify. Also, the methods current businesses take to cope with the hazards were evaluated.